Transcriptional Regulation of Müllerian Inhibiting Substance (MIS) and Establishment of a Gonadal Somatic Cell Line Using mis-GFP Transgenic Medaka (Oryzias latipes) - Kawabe, Toshiaki; Kariya, Hiroyuki; Hara, Seiji; Shirozu, Tsuyoshi; Shiraishi, Eri; Mukai, Koki; Yazawa, Takashi; Inoue, Seiya; Kitano, Takeshi (Frontiers in Endocrinology, 2020)
In vertebrate germ cell differentiation, gonadal somatic cells and germ cells are closely related. By analyzing this relationship, it has recently been reported in mammals that primordial germ cells (PGCs), induced from pluripotent stem cells and germline stem cells, can differentiate into functional gametes when co-cultured in vitro with fetal gonadal somatic cells. In some fish species, differentiation into functional sperm by reaggregation or co-culture of gonadal somatic cells and germ cells has also been reported; however, the relationship between gonadal somatic cells and germ cells in these species is not well understood. Here, we report the transcriptional regulation of Müllerian inhibiting substance (MIS) and the establishment of a gonadal somatic cell line using mis-GFP transgenic fish, in medaka (Oryzias latipes)—a fish model which offers many advantages for molecular genetics. MIS is a glycoprotein belonging to the transforming growth factor  superfamily. In medaka, mis mRNA is expressed in gonadal somatic cells of both sexes before sex differentiation, and MIS regulates the proliferation of germ cells during this period. Using luciferase assays, we found that steroidogenic factor 1 (SF1) and liver receptor homologue 1 (LRH1) activate medaka mis gene transcription, probably by binding to the mis promoter. We also report that mis-GFP transgenic medaka emit GFP fluorescence specific to gonadal somatic cells in the gonads. By fusing Sertoli cells from transgenic medaka with a cell line derived from medaka hepatoma cancer, we produced a hybridoma cell line that expresses gonadal somatic cell-specific markers, including Sertoli and Leydig cell markers. Moreover, embryonic PGCs co-cultured with the established hybridoma, as feeder cells, proliferated and formed significant colonies after 1 week. PGCs cultured for 3 weeks expressed a germ cell marker dnd, as well as the meiotic markers sycp1 and sycp3. Thus, we here provide the first evidence in teleosts that we have successfully established a gonadal somatic cell-derived hybridoma that can induce both the proliferation and meiosis of germ cells.